IMPLEMENTASI AUDIT OPERASIONAL UNTUK MENILAI EFISIENSI DAN EFEKTIVITASPENGELOLAAN AKTIVA TETAP PADA PT ASTRA GRAPHIA TBK - Maria Vania; Rosmita (CV SWA Anugrah, 2023)
Every company generally has a main goal that will be achieved by being oriented towards one goal, namely maximizing the company's operations to gain profits. Fixed assets are assets owned by an agency to support operational activities carried out by that agency. The high value of fixed assets can greatly influence the condition of financial statements. For this reason, management of fixed assets must be carried out well so that fixed assets can be optimized as efficiently, effectively, and economically as possible. In connection with this business, the company needs to conduct an audit of the management of fixed assets carried out by the relevant unit in the form of an operational audit carried out by the Internal Audit Unit (SPI). The type of research used in this research is descriptive with a non-statistical quantitative approach. Data collection techniques used were library research and documentation methods. Meanwhile, the data analysis technique used is financial ratio analysis. The conclusion from this research is that one of the company assets that needs to be maintained is fixed assets. Fixed assets for companies are purchased and used as a tool to support the company's operational activities, with the aim of generating income in the short and long term. In this regard, implementing an operational audit of fixed asset management is very important to determine the usefulness and results of these fixed assets, as well as to maintain the value of the company's fixed assets.